2016
DOI: 10.3989/mc.2016.06015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gypsum plasterboard with polyurethane foam waste reinforced with polypropylene fibers

Abstract: Gypsum plasterboard that incorporates various combinations of polyurethane foam waste and polypropylene fibers in its matrix is studied. The prefabricated material was characterized in a series of standardized tests: bulk density, maximum breaking load under flexion stress, total water absorption, surface hardness, thermal properties, and reaction to fire performance. Polypropylene fibers were added to the polyurethane gypsum composites to improve the mechanical behavior of the plasterboard under loading. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…The PU filler loading decreases the density while, the thermal resistance improves proportionally. The reaction to fire of these composites measured with the non combustibility test confirmed that taking only into account the influence of the constituents to fire development, its composition is classified as Euroclasses A2 according to European fire reaction classification of building materials for homogeneous products [14].…”
Section: Recycled Lightweight Pu Plaster Materialsmentioning
confidence: 66%
“…The PU filler loading decreases the density while, the thermal resistance improves proportionally. The reaction to fire of these composites measured with the non combustibility test confirmed that taking only into account the influence of the constituents to fire development, its composition is classified as Euroclasses A2 according to European fire reaction classification of building materials for homogeneous products [14].…”
Section: Recycled Lightweight Pu Plaster Materialsmentioning
confidence: 66%
“…Different substitutions have been made in previous studies, of plaster type A1 for rigid PU foam waste [24,25]. The conclusion was reached that the optimal ratio of components in volume could be (1/1.5), that is, 1part gypsum with 1.5 parts of polyurethane foam waste.…”
Section: The Possibilities Of the Uses Of The Wastes Studiedmentioning
confidence: 99%
“…Mainly, it is used as an interior lining material for walls, partitions and ceilings, and it can be used as a prefabricated plate or as a plaster directly applied onto walls [1]. The gypsum industry has sought to design prefabricated elements with good mechanical behaviour, fundamentally that of strength while being bent, while also having adequate thermal and acoustic properties [2][3][4].…”
Section: Introductionmentioning
confidence: 99%